Justice in Hungary Today: Third Report of the International Commission of Jurists on the Hungarian Situation and the Rule of Law: 1 September 1957 to 17 January 1958 - Héderváry, Claire de (1958)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): International Commission of Jurists - the Hague Chronological List of Sentences as reported by Hungarian Sources, 1 September 1957 to 17 January 1958.